Autoantibodies targeting interferons and GM-CSF are associated with adverse outcome risk, comorbidities, and pathogen in community-acquired pneumonia - Von Stemann, Jakob Hjorth; Dungu, Arnold Matovu; Laguarda, Maria Vispe; Ryrsø, Camilla Koch; Hegelund, Maria Hein; Faurholt-Jepsen, Daniel; Krogh-Madsen, Rikke; Hansen, Morten Bagge; Lindegaard, Birgitte; Ostrowski, Sisse Rye (Frontiers in Immunology, 2024)
Abstract Cytokine autoantibodies (c-aAb) have been associated with pulmonary diseases, including severe novel coronavirus (COVID-19) disease and pulmonary alveolar proteinosis. This study aimed to determine c-aAb association with community-acquired pneumonia (CAP) etiology (SARS-CoV-2, influenza, or bacteria), and c-aAb associations to CAP-related clinical outcomes and pulmonary comorbidities. In a cohort of 665 patients hospitalized with CAP, c-aAb targeting IFNα, IFNβ, IFNγ, IL-1α, IL-6, IL-10 and GM-CSF were measured in plasma samples. Associations between c-aAb and baseline characteristics, pulmonary comorbidities, pathogen, intensive care unit (ICU) transferal, time to clinical stability and mortality were estimated, with results stratified by sex. Men infected with SARS-CoV-2 had more high-titer type 1 IFN c-aAb compared to other pathogens. Among patients with CAP, asthma and bronchiectasis comorbidities were associated with high-titer GM-CSF c-aAb in men, and men with high-titer IFNβ c-aAb had increased odds for ICU transferal. High-titer IL-10 c-aAb were associated with faster clinical stability in women. In conclusion, in men with CAP various c-aAb – including type 1 IFN and GM-CSF c-aAb - were associated with adverse clinical events and comorbidities, whereas c-aAb targeting an autoinflammatory cytokine were associated with a positive outcome in women. This suggests that the potentially immunomodulatory effects of c-aAb depend on pathogen, autoantibody-specificity, comorbidity and sex.